Genetic variants in AKR1B10 associate with human eating behavior - Rohde, Kerstin (BMC Genet, 2015)
BACKGROUND: The human Aldoketoreductase 1B10 gene (AKR1B10) encodes one of the enzymes belonging to the family of aldoketoreductases and may be involved in detoxification of nutrients during digestion. Further, AKR1B10 mRNA (messenger ribonucleic acid) expression was diminished in brain regions potentially involved in the regulation of eating behavior in rats which are more sensitive to cocaine and alcohol. We hypothesized that the human AKR1B10 gene may also play a role in the regulation of human eating behavior. RESULTS: We investigated the effects of 5 genetic variants of AKR1B10 on human eating behavior among 548 subjects from a German self-contained population, the Sorbs, and in 350 subjects from another independent German cohort. Among the Sorbs, we observed nominal associations with disinhibition at the 5′ untranslated region (5′ UTR) variant rs10232478 and the intragenic variants rs1834150 and rs782881 (all P ≤ 0.05). Further, we detected a relationship of rs1834150 and rs782881 with waist, smoking consumption (rs782881) and coffee consumption (rs1834150) (all P ≤ 0.05). Albeit non-significant, replication analyses revealed similar effect directions for disinhibition at rs1834150 (combined P = 0.0096). Moreover, in the replication cohort we found rs1834150 related to increased restraint scores with a similar direction as in the Sorbs (combined P = 0.0072). CONCLUSION: Our data suggest that genetic variants in the AKR1B10 locus may influence human eating behavior. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12863-015-0189-9) contains supplementary material, which is available to authorized users.